Statistical Analysis of Long-term Health Effects of Thailand's Oil Spill on the Health of Spill Cleaners - Owusu, Benjamin Atta (Prince of Songkla University, 2023)
Thesis (Ph.D., Research Methodology)--Prince of Songkla University, 2022